The Tradition of Basuluk: Its Influence on the Religious Understanding of Naqshbandi Order Followers in Padang City - Yuliana Nurfalina; Erman Erman; Erasiah Erasiah (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
Suluk is an activity by isolating oneself or calming oneself down in a quiet and calm place, by carrying out acts of worship such as reciting dhikr, performing prayers, fasting, making istigfar, and other practices. This suluk activity is a form of activity carried out by the congregation or followers of the Naqshbandi Tarekat, one of which is the Naqshbandi Tarekat in Padang City. The method used in this research is the historical method by analyzing literature studies (Library Research). Similar to the congregation or followers of the Naqshbandi Order in Padang City, this suluk has also become a tradition for the religious spiritual activities of the congregation or its followers, which is carried out twice a year. With the suluk activity which is considered a tradition that is always carried out by the congregation or followers of the Naqshbandi Tarekat in Padang City, it has a positive impact on the development of religious understanding of the Naqshbandi Tarekat followers in Padang City, because they can focus more on learning about religion, worship, improving oneself, and other practices, should be done in a quiet place and away from crowds.